2012
DOI: 10.1111/aji.12065
|View full text |Cite
|
Sign up to set email alerts
|

Cutting‐Edge Report: TLR10 Plays a Role in Mediating Bacterial Peptidoglycan‐Induced Trophoblast Apoptosis

Abstract: Problem There is a strong correlation between intrauterine bacterial infection and preterm labor. While inflammation is a common mechanism, certain pathogens may trigger placental apoptosis. TLR2 activation by gram-positive bacterial peptidoglycan (PDG) induces first trimester trophoblast apoptosis and decreased IL-6 secretion. This is dependent upon the presence of TLR1 and the absence of TLR6, both TLR2 co-receptors. Since TLR10 is also a TLR2 co-receptor, the objective of this study was to determine its exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 14 publications
(53 reference statements)
0
32
0
Order By: Relevance
“…Mulla et al provide evidence that TLR10, which is expressed on trophoblast during gestation, induces apoptosis through activation of caspase-3 (7). Mulla et al also found the trigger for this response to be a TLR2 ligand (i.e., peptidoglycan); no effect on IL-6 production was found in these studies (7). Very recently, a study described that TLR10 acts as a proinflammatory TLR, which is the opposite of the suppressive function of TLR10 we report here (19 PBMCs from individuals without polymorphisms (wt; wild-type; white bars), individuals with the I369L SNP (D) or I775V SNP (E) in one of both alleles (he; heterozygous; gray bars), and individuals with the SNP in both alleles (ho; homozygous; black bars), were stimulated for 24 h at 37°C with RPMI, or B. burgdorferi.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Mulla et al provide evidence that TLR10, which is expressed on trophoblast during gestation, induces apoptosis through activation of caspase-3 (7). Mulla et al also found the trigger for this response to be a TLR2 ligand (i.e., peptidoglycan); no effect on IL-6 production was found in these studies (7). Very recently, a study described that TLR10 acts as a proinflammatory TLR, which is the opposite of the suppressive function of TLR10 we report here (19 PBMCs from individuals without polymorphisms (wt; wild-type; white bars), individuals with the I369L SNP (D) or I775V SNP (E) in one of both alleles (he; heterozygous; gray bars), and individuals with the SNP in both alleles (ho; homozygous; black bars), were stimulated for 24 h at 37°C with RPMI, or B. burgdorferi.…”
Section: Discussionmentioning
confidence: 73%
“…TLR10 is predominantly expressed in tissues rich in immune cells, such as spleen, lymph node, thymus, tonsil, and lung (2). Expression of TLR10 can be induced in B cells, dendritic cells, eosinophils, and neutrophils (3,5,6), as well as on nonimmune cells, such as trophoblasts (7). TLR1 and TLR6 are known to form heterodimers with TLR2, and this was shown for TLR10 as well (3,8).…”
mentioning
confidence: 97%
“…Detection of TLR2, TLR4 and TLR10 mRNA is supported (Abrahams et al, 2004, Mulla et al, 2013), but has not previously been collectively addressed, which is required to fully understand the functionality of these receptors. The gene expression findings indicate a potential for diverse TLR signaling in primary trophoblasts, and are supported functionally by cell surface TLR2/1, TLR4 and TLR5…”
Section: Discussionmentioning
confidence: 99%
“…and TLR10 expression have been demonstrated in primary first trimester trophoblasts (Abrahams et al, 2004, Mulla et al, 2013 and of the endosomal TLRs, only TLR3 and TLR8 transcripts have been detected in early gestational placentas (Abrahams et al, 2005, Aldo et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation